If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(1/2)*x-((3/4)*x)-((3/2)*x)+5/8-(5/2) = 0
(1/2)*x+(-3/4)*x+(-3/2)*x+5/8-5/2 = 0
-7/4*x-15/8 = 0 // + 15/8
-7/4*x = 15/8 // : -7/4
x = 15/8/(-7/4)
x = -15/14
x = -15/14
| d=60(8) | | (x^2-x-2)/(x^2-4) | | y=-3*1-6 | | 6x-3+5=7 | | 3/4t-7/12t=1 | | 2/3m=46 | | 2/5x-1=-6 | | 38.13x-7.26=13.48-1691x | | 297/8-2x=27.5 | | 3+(1/x-2)=27 | | -10x+6=-7x+-9x | | 100x=1.222222 | | 69x=34x | | 3d=-3+3d | | p^2-12p+76=0 | | x+-3=-91 | | x^2/2-1=-7/4x | | 0=k-k | | 1.5x-.25x=8+4x | | ((6x+6)/7)*(14/(x^2-1)) | | 11x-11/2(x-2)=22 | | 10-9m+-10-7m= | | 8x/2(x+2) | | 10=5x-4x-5 | | -5.6(4.5x+4.51)=-1.8(2.6x-4) | | (3x+2)^9/(3x+2)^6 | | 1/8(16y+8)=1/4(8y-16) | | 4(6p-2)=-8-2p | | 7-y=-18 | | -10b-45=3(b-15) | | -4x+6=-2x+5 | | y=-3/5*1+6 |